Pembrolizumab for the treatment of progressive multifocal leukoencephalopathy following anti‐CD19 CAR‐T therapy: a case report. Issue 4 (4th August 2021) - Mackenzie, Strachan; Shafat, Manar; Roddy, Harriet; Hyare, Harpreet; Neill, Lorna; Marzolini, Maria A. V.; Gilhooley, Michael; Marafioti, Teresa; Kara, Eleanna; Sanchez, Emilie; Rees, Jeremy; Lynch, David S.; et al.
Abstract: Progressive multifocal leukoencephalopathy (PML) is an opportunistic brain infection with few treatment options and poor survival when reversal of the underlying immune dysfunction is not achievable. JC polyomavirus reactivation resulting in PML can rarely complicate chimeric antigen receptor T‐cell (CAR‐T) therapy. We describe successful treatment of PML with Programmed death‐1 (PD‐1) blockade using pembrolizumab, 4 months following axicabtagene ciloleucel. Radiological features of immune reconstitution inflammatory syndrome without clinical deterioration were seen. Evidence of anti‐viral immune reconstitution by in vitro detection of JC‐specific T‐cells and sustained neurological recovery in this patient suggest PD‐1 blockade may be an effective treatment approach for PML post‐CAR‐T.